Nikmat dalam Surat Al-Kautsar (Studi Tafsir Al Munir) - Naila Falah, Khodijah; Sulthoni, Akhmad (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
This study examines the favors in Surah Al-Kautsar according to Prof. Wahbah Az-Zuhaili in Tafsir Al-Munir. Tafsir al-Munir is a tafsir that examines the verses of the Qur'an in a comprehensive, complete, and covers various aspects needed by the reader. The explanation and determination of the laws are deduced from the verse of the Qur'an with a broader meaning, accompanied by the causes of the descent of the verse balaaghah (rhetoric), I'raab (syntax), as well as linguistic aspects. This study aims to analyze the blessings in Surah Al-Kautsar according to Prof. Wahbah Az-Zuhaili in Tafsir Al-Munir. The results of the analysis show that Tafsir Al-Munir explains the cause of the revelation of Surah Al-Kautsar, the content of the verse and some aspects that can be done in everyday life. This study also explains that Surah Al-Kautsar explains that Allah has given so many favors to the prophet Muhammad Saw. and his people. So, we should be grateful for these favors by praying sincerely and slaughtering with the concept of tawhid to Allah Ta'ala.